Non-invasive SARS-CoV-2 RNA detection and human transcriptome analysis using skin surface lipids - Kuwano, Tetsuya; Kanno, Takayuki; Tobiume, Minoru; Hirata, Yuichiro; Katano, Harutaka; Koga, Michiko; Nagai, Hiroyuki; Tsutsumi, Takeya; Yoshikawa, Noritada; Yotsuyanagi, Hiroshi; Kutsuna, Satoshi; Miyazato, Yusuke; et al. (Scientific reports, 2024)
There have been several reports of skin manifestations in patients with coronavirus disease 2019 (COVID-19). However, it is unclear whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA can be detected on the skin surface, including the sebum, of these patients. In this study, SARS-CoV-2 RNA was detected using real-time reverse-transcription polymerase chain reaction (RT-PCR) assay of skin surface lipids (SSLs) collected using an oil-blotting film from the faces of hospitalized patients with COVID-19. Human transcriptome analysis was also performed using the same samples. In facial SSLs of patients with COVID-19, the RT-PCR positivity rate was 84.6% (11/13 samples) within 5 days and 30.4% (7/23 samples) by 6–10 days of symptom onset. In the transcriptome analysis, the most characteristic SSL-RNA profile was the upregulation of interferon-stimulated gene (ISG)-related genes, such as ISG15 , IFITM1 , and MX1 . This study presents an alternative technique using SSLs for non-invasive SARS-CoV-2 RNA detection and simultaneous analysis of human molecular pathogenesis in patients with COVID-19.